Antihyperglycemic and glucose tolerance activity of ficus deltoidea ethanolic extract in diabetic rats - Zainah Adam,; Muhajir Hamid,; Amin Ismail,; Shafii Khamis,; Norazizah Marsidi, (Penerbit UKM, 2010)
Ficus deltoidea or Mas cotek is one of the common medicinal plants used in Malaysia has been claimed to have antidiabetic activity. However, scientific evidence to confirm its efficacy is still lacking. Thus, the present study was undertaken to evaluate the potential of ethanolic extract of Ficus deltoidea to reduce hyperglycaemia in streptozotocininduced diabetic rats at different prandial state. The results showed that, ethanolic extract of Ficus deltoidea significantly reduced fasting and postprandial hyperglycemia particularly after 4 and 6 hours of extract administration. Likewise, glucose tolerance activity was significantly improved in the presence of Ficus deltoidea ethanolic extract at a low dose, 100 mg/kg. It is suggested that ethanolic extract of Ficus deltoidea at particular doses, possess fasting and postprandial antihyperglycemic activity as well as glucose tolerance activity in streptozotocin-induced diabetic rats.